Invention in medicine and dentistry: optimizing blood oxygen saturation ratio by assisted drainage therapy - Utomo, Kimberley Clarissa; Utomo, Haryono; Witjaksono, Widowati (2014)
Oxygen consumption is very important starting from inside mother’s womb and throughout life. Decrease of oxygen intake is disadvantageous to our body. Common symptoms from the mildest are drowsiness, blurred vision, headache, increase of blood pressure, and the worst are unconsciousness to death. The integrated orofacial massage is a new invention in medicine and dentistry which is able to increase oxygen saturation/pulse (SpO2) ratio as well as, relief asthma and migraine symptoms within minutes. It is consisted of scaling and root planning that accompanied with gingival and cheek muscles massages. The purpose of this study is to investigate the effectiveness of assisted drainage therapy (ADT) to increase SpO2. Methods: Retrospective study of 30 randomly selected samples from 150 patients who suffered from sinusitis, asthma, migraine and vertigo; and had undergone ADT were investigated for comparison of SpO2 ratio using pulse oxymeter. The statistical analysis was done using T-test pre and post ADT. Result: Difference between pre and post ADT SpO2 ratio was highly significant (p = 0.001). Conclusion: ADT was very effective in increasing SpO2 ratio. Therefore, it can optimize blood oxygen thus also improve general health. This study suggested that collaboration research with medical researchers is mandatory to verify the successful result